In vitro assessment of needle and irrigant penetration when using different irrigation needle tips - Saleha Hussain; Lars Bjørndal; Merete Markvart (Biomaterial Investigations in Dentistry)
Objective: The aim of this study was to compare the needle and irrigant penetration depth of a newly developed multi-vented polymer needle (30G), with three established needle designs – an open-ended metal needle (30G), a side-vented polymer needle (30G), and a notched metal needle (27G) used as a reference control. The effect of manual dynamic activation (MDA) was also measured. The null hypotheses were that the irrigant penetration would be the same regardless of needle tip, and the addition of MDA would make no difference in terms of irrigant penetration.